2016
DOI: 10.3171/2015.6.jns142965
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar liponeurocytoma: a rare intracranial tumor with possible familial predisposition. Case report

Abstract: C erebellar liponeurocytomas are typically lowgrade tumors that arise in the cerebellar hemispheres or vermis and contain cells of neuronal, astrocytic, and lipomatous differentiation. 17 The biology and long-term outcomes of these tumors are undefined, and to our knowledge, familial occurrences have not been described. We present here the case of a young woman with a cerebellar liponeurocytoma and multiple immediate family members, including her mother, with similar lesions. This report describes the tumors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…[8] Recent reports also exist in the form of individual cases, the most common being in the infratentorial location. [910111213] Gembruch et al ., in a systematic review of all the reported cases ( n = 73) until 2018, noted that these tumors had low MIB-1 proliferation index (3.73 ± 4.01%). [14] Of the infratentorial location, the cerebellar hemisphere is the most common location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Recent reports also exist in the form of individual cases, the most common being in the infratentorial location. [910111213] Gembruch et al ., in a systematic review of all the reported cases ( n = 73) until 2018, noted that these tumors had low MIB-1 proliferation index (3.73 ± 4.01%). [14] Of the infratentorial location, the cerebellar hemisphere is the most common location.…”
Section: Discussionmentioning
confidence: 99%
“…In recent articles,[1011] a familial predisposition has been suggested with possibly an autosomal dominant mode of inheritance. However, a causative genetic mutation as well the cell of origin of liponeurocytoma is yet to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings, large cell/anaplastic medulloblastomas are associated with C-MYC or N-MYC amplifications [ 23 ]. Despite this, Wolf et al [ 24 ] and Pikis et al . [ 16 ] suggested an inheritable predisposition for tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in 1978 by Bechtel et al [2], and nearly 50 cases under several synonyms have been reported since [11,26,32,33]. In the 2000 World Health Organization (WHO) classification of Tumors of the Central Nervous System it was categorized for the first time as a distinct entity within the neuronal and mixed neuronal-glial tumors section.…”
Section: Introductionmentioning
confidence: 99%
“…also occur supratentorially. Single cases suggesting familial predisposition for such tumors have been published recently [26,33].…”
Section: Introductionmentioning
confidence: 99%